2017
DOI: 10.1039/c7ra02013a
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phase tuning of α- and β-MnO2nanocacti evolved at varying modes of acid count for their well-coordinated energy storage and visible-light-driven photocatalytic behaviour

Abstract: A simple hydrothermal method is developed to synthesize two different phases, a and b of MnO 2 nanocacti (comprising nanowires with 1-10 nm diameter self assembled by ultrathin sheets) as well as MnO 2 nanorods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 62 publications
1
36
0
2
Order By: Relevance
“…28 Also, a owery MnO 2 /graphene complex was prepared using GO and MnSO 4 as the raw material via electrochemical deposition, and in a three-electrode system, the specic capacitance can reach 595.7 F g À1 at the current density of 1 A g À1 . 29 Previously, MnO 2 with different microstructures has been successfully prepared and tested, [30][31][32][33][34][35] and the results show that different structures of the same materials demonstrate different electrochemical properties. Zhu et al 36 reported a core branch heterostructure nano array of a-MnO 2 nanowires and b-MnO 2 ultra-thin nanosheets that combined the mass load of the active substance with enhanced pseudocapacitance.…”
Section: Introductionmentioning
confidence: 99%
“…28 Also, a owery MnO 2 /graphene complex was prepared using GO and MnSO 4 as the raw material via electrochemical deposition, and in a three-electrode system, the specic capacitance can reach 595.7 F g À1 at the current density of 1 A g À1 . 29 Previously, MnO 2 with different microstructures has been successfully prepared and tested, [30][31][32][33][34][35] and the results show that different structures of the same materials demonstrate different electrochemical properties. Zhu et al 36 reported a core branch heterostructure nano array of a-MnO 2 nanowires and b-MnO 2 ultra-thin nanosheets that combined the mass load of the active substance with enhanced pseudocapacitance.…”
Section: Introductionmentioning
confidence: 99%
“…31 Therefore, MnO 2 -based systems could be usefully exploited in curbing environmental pollution and promoting water purification and safety, thanks also to their low toxicity, moderate price and high activity. 6,15,[32][33][34] So far, MnO 2 materials have been used for the photodegradation of organic dyes in wastewater. 1,5,6,11,13,34 In a different way, reports on the reversible hydrophobic/hydrophilic switching and on solid phase photoactivated pollutant degradation have been devoted to TiO 2 4,35,36 and other oxide materials, 7,8 but, to our knowledge, no MnO 2 -based systems have ever been investigated for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,13,22,38 ), which, in turn, can be tailored by the adopted synthetic method. 12,16,33 As a consequence, efforts have been dedicated to the fabrication of low-dimensional MnO 2 systems using various techniques, 29,34,39,40 among which liquid-phase routes are by far the most used. 6,9,11,14,16,32 However, several studies have been dedicated to powders, 5,9,10,12,26,30,40 whereas supported MnO 2 systems, though being undoubtedly preferable for various applications, 7,36,41,42 are indeed much less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Диоксид марганца также находит применение в составе катализаторов окисления NO [18], толуола [19], ацетальдегида при комнатной температуре [20], озонирования 4-нитрофенола [21], дожига диметилового эфира [22], разложения трет-бутилгидропероксида [23] и др. В модельных реакциях разложения таких красителей, как конго красный [24][25][26], метиловый оранжевый [25,26], метиленовый голубой [27,28], родамин B [26], и в более сложных реакциях одностадийного гидролиза нитрилов до амидов [29] и деградации метилпаратиона [30] была продемонстрирована высокая фотокаталитическая активность диоксида марганца. Его несомненными преимуществами являются активация светом видимого диапазона и сохранение фотокаталитической активности при многократном циклировании.…”
Section: Introductionunclassified
“…Вместе с тем, наиболее технологичными являются синтетические схемы, обеспечивающие получение продукта с заданным фазовым и морфологическим составом за счет варьирования параметров синтеза (температуры, концентрации исходных реагентов, pH среды и т.п.) [7,25]. Так, ранее нами была предложена методика синтеза диоксида марганца в условиях гидротермально-микроволновой обработки в присутствии меламина [39] и показана принципиальная возможность селективного синтеза различных полиморфных модификаций MnO 2 в гидротермально-микроволновых условиях с использованием гексаметилентетрамина (ГМТА) [40].…”
Section: Introductionunclassified